SPE Asia Pacific Oil and Gas Conference 1994
DOI: 10.2118/28779-ms
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic Fracturing Experiments in the Great Northern Coal Seam

Abstract: Two field-scale hydraulic fracturing experiments were performed in vertical boreholes on the lease of Munmorah Colliery located south of Newcastle, NSW. The treatments fractured the 3-metre thick, 220-metre deep Great Northern coal seam and were designed to provide a direct comparison between a borate-crosslinked gel and a water treatment. The fracture geometries were mapped during mining of the coal seam. Geologic mapping disclosed a well-defined coal face cleat and systematic full-seam join… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] et al 1 investigated how well the fractures are contained in coal during a stimulation treatment. In this study, 12 vertical wells were drilled, completed, and subsequently evaluated via mining excavation.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] et al 1 investigated how well the fractures are contained in coal during a stimulation treatment. In this study, 12 vertical wells were drilled, completed, and subsequently evaluated via mining excavation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They mentioned that these needed to be accounted for during stimulation treatments and also presented a new method to calculate fracture width in shallow coal seams. Jeffrey, et al 11 investigated the difference in fracture geometries created when one well was stimulated with borate-crosslinked gel and the other with a water treatment. The target coal seam was the Great Northern coal seam of Australia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In beach-bar sandstone reservoirs, the thickness of single production layer (sandstone) is very small (usually less than 2.0 m, and even less than 1.0 m) and mudstone The typical multiple rock layers and the observed complex fracturing modes in field, (a) the sedimentary characteristics of bar sand subfacies and beach sand subfacies in one of beach-bar sandstone reservoirs in Shengli Oilfield of China [3]; (b) outcrop of a shale formation, where the horizontal beddings are cut by the vertical fractures (denoted by red dashed line) to form fracture networks, Well A and B are the conceptual vertical and horizontal wells [8]; and (c) a hydraulic fracture that grew vertically in a coal seam and horizontally along the interface between the coal and the roof rock (the hydro-fracture is shown in yellow and the black arrows represent the fracturing direction) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Jeffrey et al 7 studied the influence of bedding, face cleats and joints on the fracture geometry. Gu et al 8 proposed an interfacial slip model based on the displacement discontinuity method.…”
mentioning
confidence: 99%
“…Taking an example of Shuping landslide, Wang et al 6 found that the deformation of Shuping landslide corresponds to the Three Gorges reservoir fluctuations, especially, the deformation of the landslide is more active during periods of declining reservoir levels. Continuous rainfall also triggers the failure of slope, because the strength of the sliding zone is reduced by water infiltration 7 . Besides, Burda et al 8 proposed that the climate change induces reactivation of landslide.…”
mentioning
confidence: 99%